Successful Modified Chemotherapy Regiment in Patient with Hairy Cell Leukemia Variant - Hermanto, Djoko Heri; Hatinah, Amalia Nurul; Arifah, Nina Nur (Clinical and Research Journal in Internal Medicine, 2025)
Hairy Cell Leukemia variant (HCLv) is distinct from Hairy Cell Leukemia classic (HCLc) and categorized as an unclassified splenic B-cell lymphoma/leukemia. HCLv is a rare disease with a 15% survival rate after 15 years, and accounts for only 0.4% of chronic lymphoid malignancies and the etiology remains unclear. In this context, it responds poorly to standard Hairy Cell Leukemia (HCL) therapy. The primary complaints of a 64-year-old patient on admission were weight loss, early satiety, fatigue, and abdominal enlargement. Physical examination showed massive splenomegaly, and laboratory results showed thrombocytopenia and leukocytosis with a predominance of lymphocytes. Meanwhile, bone marrow puncture (BMP) and flow cytometry results showed hairy cells with morphology and immunophenotyping consistent with HCLv. Due to the unavailable purine analogs, and considering potential outcomes, the patient was treated with a combination of Cytarabine, Daunorubicin, and Rituximab for 5 days. After 3 months, clinical improvement was observed, and BMP evaluation showed no evidence of hairy cells projection, leading to the patient being declared in complete remission. This case presents a new therapy regimen that has not been previously applied to HCLv cases and it may serve as an option for similar cases, subject to clinician judgment and patient preferences. Keywords: HCL variant, modified chemotherapy regimen, total remission